MATAHARI DALAM AL-QUR`AN DAN ASTRONOMI: INTEGRASI ILMU TAFSIR DAN SAINS - Ahmad Mujahid; Arizal Hangga Tri Setya, Rihan Faza Sahana, Rehan Ariansyah Putra (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
This study explores the integration of the Qur'anic interpretation (tafsir) and modern astronomy in understanding the sun’s role as described in the Qur’an. The sun, classified as a star, sustains life on Earth through nuclear fusion, influences climate, and governs celestial mechanics. The Qur’an uses distinct terms such as siraj (lamp), dhiya’ (blinding light), and nur (reflected light) to highlight the sun’s unique characteristics compared to other celestial bodies. These descriptions align with scientific findings, including the sun’s self-generated energy, gravitational role in the solar system, and its function in determining religious practices like prayer and fasting. Previous studies confirm the Qur’an’s alignment with astronomical discoveries, emphasizing the need for interdisciplinary integration to deepen both spiritual and scientific comprehension. This research employs qualitative- descriptive methods through library research, analyzing tafsir literature and scientific data to demonstrate the harmony between divine revelation and empirical science. The findings underscore the sun’s cosmological and theological significance, reinforcing the Qur’an’s timeless relevance in explaining natural phenomena.